RailsSpace Ruby on Rails : tutorial - Prochazka, Aurelius (LiveLessons., 2007)
"Ruby on Rails has emerged as today's most powerful, useful Web development framework. RailsSpace Ruby on Rails Tutorial makes real-world Rails development easier than ever before. In fifteen targeted video sessions, Rails expert Aurelius Prochazka walks you through every step of building RailsSpace, a full-fledged social networking site. You'll learn at your own pace, as you move from a static page to a robust, highly dynamic site. You'll walk step-by-step through implementing user registration, authentication, profiles, image uploads, blogs, searches, and more. Along the way, you'll master all the Rails techniques you'll need ... from Model-View-Controller architecture to automated testing, refactoring to REST."--Resource description page